King's Cutters and Smugglers 1700-1855 - Chatterton, E. Keble (Edward Keble), 1878-1944 (Salt Lake City, UT : Project Gutenberg, 2006)
"King's Cutters and Smugglers 1700-1855" by E. Keble Chatterton is a historical account written in the early 20th century. The book delves into the rich and adventurous history of smugglers and the King's Preventive Service during the 18th and early 19th centuries. It aims to provide a factual representation of the smuggling era, showcasing the daring exploits of smugglers and the methods used by the Revenue cutters to combat them. The opening of the book sets the stage for an in-depth exploration of the smuggling trade and the response from the English government. It emphasizes the historical significance of this period, framing smuggling as a complex and enduring issue that involved not just individual criminals, but whole communities that rallied around the smugglers. Chatterton highlights the ongoing fascination with smugglers, who were often viewed as rebellious figures defying authority, while also acknowledging the challenges faced by the Preventive forces tasked with upholding the law. The author indicates a wealth of research based on authentic records, aiming to provide accurate narratives that contrast with the romanticized tales often told in fiction. (This is an automatically generated summary.)
Release date is 2006-01-21
E-text prepared by Steven Gibbs, Jeannie Howse, and the Project Gutenberg Online Distributed Proofreading Team (https://www.pgdp.net)
Keywords: Smuggling -- Great Britain -- History; Customs administration -- Great Britain -- History; Great Britain -- Commerce -- History -- 19th century; Great Britain -- Commerce -- History -- 18th century